Highly sensitive and convenient aptasensor based on Au NPs@Ce-TpBpy COF for quantitative determination of zearalenone. Issue 27 (13th June 2022) - Chen, Zhixiong; Yang, Meng; Li, Ziying; Liao, Wenchun; Chen, Bengqi; Yang, Tong; Hu, Rong; Yang, Yunhui; Meng, Shuang
Abstract : An aptasensor based on a portable U-disk electrochemical workstation is demonstrated for the quantitative determination of zearalenone. The aptamer sensor exhibited excellent sensitivity, selectivity, reproducibility. Abstract : In this work, an aptasensor based on a portable U-disk electrochemical workstation in combination with a screen-printed electrode (SPE) is demonstrated for the quantitative determination of zearalenone (ZEN). The aptamer is immobilized on Au NPs@Ce-TpBpy COF (Covalent organic frameworks), which is modified on the surface of glassy carbon electrode. ZEN specifically binds to ZEN aptamer, which hinders the electron transfer and decreases the catalytic current of Au NPs@Ce-TpBpy COF for the reduction of hydrogen peroxide, measured by chronoamperometry ( i – t ). The quantitative detection of ZEN toxin is realized by a decrease of the catalytic current (Δ I ). Under the optimal experimental conditions, the aptamer sensor exhibited excellent sensitivity, selectivity, reproducibility. A wide linear range of 1 pg mL −1 –10.0 ng mL −1 with a detection limit of 0.389 pg mL −1 (at 3 σ ) was obtained. The linear equation is Δ I = 0.401 lg  c + 1.948 with a correlation coefficient of 0.9906. The recovery is in the range of 93.0–104.7% for the cornflour samples. The proposed method offers a new strategy for the rapid, inexpensive, and real-time detection of ZEN.